Implementasi Metode TOPSIS Untuk Penentuan Finalis Duta Wisata Joko Roro Kabupaten Malang (Studi Kasus : Paguyuban Joko Roro) - Krisna Andryan Syahputra Effendi; Edy Santoso; Nurul Hidayat (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Each district and the cities in Indonesia have a separate icon to showcase their respective regions. Start from the culture until the potential of tourism object. One of the most well known icon until the territory was visited by many tourists is tourism object. This is shown by the number of domestic tourists and also foreign tourists who visited in each area in Indonesia one of the Malang Regency. Malang Regency rich natural tourism potential and other tourism. Therefore this Regency nicknamed